2020
DOI: 10.1002/cbf.3525
|View full text |Cite
|
Sign up to set email alerts
|

Dual in vitro invasion/migration suppressing and tamoxifen response modulating effects of a recombinant anti‐ALCAM scFv on breast cancer cells

Abstract: It has been shown that overexpression of activated leukocyte cell adhesion molecule (ALCAM) is involved in development of resistance to tamoxifen therapy and promotion of cell invasion, migration and metastasis in ER+ breast cancer cells. Thus, we hypothesized that blockade of ALCAM interconnections with antibodies could be an effective approach for reversing mentioned negative events associated with ALCAM overexpression in breast cancer cells. Here, an anti‐ALCAM scFv was recombinantly expressed and used thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Similar to our results, they showed that knockdown of ALCAM enhanced 4‐hydroxytestosterone induced cell death in tamoxifen resistant breast cancer cell line 46 . Darvishi et al, 47 in a further study described that ALCAM blockade resensitized resistant breast cancer cells to tamoxifen. The role of ALCAM in ENZA resistance of PC has not been revealed yet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our results, they showed that knockdown of ALCAM enhanced 4‐hydroxytestosterone induced cell death in tamoxifen resistant breast cancer cell line 46 . Darvishi et al, 47 in a further study described that ALCAM blockade resensitized resistant breast cancer cells to tamoxifen. The role of ALCAM in ENZA resistance of PC has not been revealed yet.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, they showed that knockdown of ALCAM enhanced 4-hydroxytestosterone induced cell death in tamoxifen resistant breast cancer cell line. 46 Darvishi et al, 47 between ENZA/ABI and DOC responsive patients. Our results however, need to be confirmed in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, a great deal has yet to be learned here. Another recent report by Darvishi et al [141] has shown that a recombinant protein that has anti-ALCAM scFv feature was able to suppress the growth of tamoxifen-resistant MCF-7 cells and synergistically enhance the anti-tumour effect of tamoxifen. The same was observed with MDA MB 231 cells.…”
Section: Alcam As a Therapeutic Targetmentioning
confidence: 98%
“…For example, the scFv directed against activated the leukocyte cell adhesion molecule (ALCAM), which is involved in the development of tamoxifen resistance, an endocrine therapeutic agent that antagonizes the proliferative effect of estrogen in breast cancer tumor cells and promotes invasion, migration, and metastasis in ER+ cells. The anti-ALCAM scFv pretreatment enhanced the antiproliferative effects of tamoxifen against resistant cell lines, thus reducing migration and invasion [ 150 ].…”
Section: Single-chain Variable Fragments (Scfv)mentioning
confidence: 99%